Insights into the determinants of innovation in energy efficiency - Marius Ley (ETH Zurich, KOF Swiss Economic Institute, 2010)
Given the increasing interest in understanding (and supporting by means of public policy) innovative activity related to energy efficient technology (EET), I attempt to identify firm-level determinants of innovation and research in this field. A novel dataset of Swiss firms has been assembled by means of a survey in 2009, resulting in more than 2300 observations featuring various indicators of innovative activity and success. Applying standard econometric methodology, I find sizeable differences of the explaining factors of energy efficiency related innovation as compared to overall innovation. In particular, market environment related variables important for overall innovative activity seem to have little explanatory power for EET related innovation, raising the question whether such innovation sufficiently responds to current and potential future demand.
Keywords: O31; Q49; 330; Innovation; Energy; Energy Efficiency; Innovation; Energieeffizienz; Technologiewahl; Schweiz